Pengembangan LKPD Berbasis HOTS Menggunakan Aplikasi Canva pada Materi Indonesia Masa Reformasi di Kelas XII SMA Negeri 1 Percut Sei Tuan - Jones Febryn Simamora; Ricu Sidiq; Yudi Roswandi; Abdi Waruwu; Jepri Alexsander Padang (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2026)
This study aims to develop Student Worksheets (LKPD) based on Higher Order Thinking Skills (HOTS) using the Canva application on the material of Indonesia during the Reformation Period and to determine the level of feasibility of the developed product. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of material experts, media experts, and grade XII students. The research instruments were in the form of expert validation questionnaires and student response questionnaires. The results showed that the LKPD was declared suitable for use. The validation of material experts obtained an average percentage of 63.33% with a feasible category, while the final stage of media expert validation obtained an average percentage of 99.09% with a very feasible category. The student response test in the small group obtained a percentage of 86.25% and the large group 92.91%, both of which were in the very interested category. These results indicate that HOTS-based LKPD using Canva is interesting and suitable for use in history learning. Based on the research results, it can be concluded that the HOTS-based LKPD developed is suitable for use as supporting teaching materials for learning and has the potential to improve students' high-level thinking skills.